Chalenging Issues In Learning Listening: A Correlational Study In University Level - Ardhani, Raden Rara Vivy Kusuma (Journal of English and Education (JEE), 2012)
Listening is one of the four skills that have an important role in mastering the target language, especially in the university level. This skill is very useful to help college students to do some academic activities that involve attending lectures or speeches, presenting materials or finding some resources to do their assignments. However, listening skill cannot be developed well due to some problems. Based on a research, listening problems include lack of vocabulary mastery, less understanding grammatical forms, e.g: speakers' utterances, unclear pronunciation and speed of speech, unclear contents of the passages, and physical setting including uncomfortable class; and lack of facility and background noise. The data is proven by the achievement of listening test that indicates that students who have listening problems tends to have low achievement in the class. To overcome this problem, lectures have to design specific instructional design to solve the listening problems. This paper will discuss more about listening problems and the appropriate learning strategies to solve the problems.Key words: instructional design, listening skills, college students